PENGARUH KEBIJAKAN RASIONALISASI ANGGARAN TERHADAP PELAKSANAAN APBD PEMERINTAH DAERAH PROVINSI RIAU TAHUN ANGGARAN 2018 - Ilham Azhari; Mexsasai Indra; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Local government budgets of Riau Province have deficits. The local government of Riau Province assigns budget rationalization policy to the implementation of the regional budget. this research intends to find out impact budget rationalization policy towards the implementation of regional budget and learn any factor causative local government applies budget rationalization policy.This research is sociological law research because it is based on field research using the interview method as primary data supported by library research as secondary data. this study uses qualitative data analysis and produces descriptive data.Conclusions in this research, first are concluded that budget rationalization policy has an impact very influential to Local government department indicative funding ceilings for all department local governments, but not very impactful to Riau province development. second, the factor causative applied factor budget rationalization policy because local revenue that received not according to revenue target.The author's advice is, first, to the regional government of Riau province, please use the budget principles appropriate with the general principles of regional financial. second, within in preparing the budget should more carefully in setting the regional revenue target. because planning is the key to success towards good regional financial governanceKeywords: Impact – Local Government Budget - Deficit